Vision 2030 Jamaica year in review 2015/16 : national development plan (Vision 2030 Jamaica Secretariat Kingston 5JM, 2016)
Provides a summary of key activities undertaken to support Plan implementation, monitoring and evaluation
Keywords: DEVELOPMENT PLANS